Influência da suplementação do fator de crescimento epidermal (EGF) em diferentes momentos da maturação in vitro de oócitos caninos - Pereira, Leda Maria Costa [UNESP]; Bersano, Paulo Ricardo de Oliveira; Lopes, Maria Denise [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2017)
The aim of this study was to evaluate the influence of epidermal growth factor (EGF) on in vitro maturation of canine oocytes at different times of the process. Ovaries were collected from 55 bitches considered healthy and aseptically isolated, immersed in physiological solution (0.9% NaCl) and transported under refrigeration. Grade 1 cumulus-oocyte complexes (COCs) were selected and divided into two groups: control group (CG) and treatment group (TG). In CG 698 grade I COCs were placed in 4-well plates containing TCM-199 medium supplemented with 25 mM HEPES, 100 IU/mL penicillin, 100 mg/mL streptomycin, 26 mM sodium bicarbonate, 1.5 mM sodium pyruvate, 2.9 mM sodium lactate pentahydrate, 0.6 mM cysteine, 0.03 IU/mL hCG, 0.5 µg/mL FSH, 20 µg/mL estrogen at 38.5oC in a humidified atmosphere of 5% CO2 in times of 24 h, 48 h, and 72 h. In TG 547 COCs received the same maturation medium plus 10 ηg/mL EGF. Logistic regression models (SAS, 2011) were constructed in order to estimate the chances of oocytes being observed at nuclear maturation stages in different culture times (24 h, 48 h, and 72 h). Based on the results found EGF-supplemented medium showed 2.56 times more chances of having an oocyte at metaphase I (M-I) than medium without EGF (p < 0.0001). The results of this study demonstrated that the time of 72 h showed 5.88 times more chances of having an oocyte at metaphase II (M-II) compared to time of 24 h (p = 0.0001) and 7.69 times more chance than time of 48 h (p = 0.0001). The chances of finding an oocyte at M-II were also 9.09 times higher in medium supplemented with EGF than in medium without EGF (p = 0.0001). Thus, these results demonstrated the essential importance of EGF at different moments of oocyte maturation, being a key component for the acquisition of meiotic competence in bitches, increasing the M-I and M-II rates.
Influence of epidermal growth factor (EGF) supplementation at different times of in vitro maturation of canine oocytes
Keywords: Bitches; Competence; Egf; Oocyte